Human resource management practices on organizational commitment the islamic perspective / Siti Rokiah Salleh - Salleh, Siti Rokiah (2016)
This study was conducted to observe the management of human resources from the Islamic perspective and its effects on organizational commitment among selected employees in Majlis Perbandaran Kota Bharu Bandar Raya Islam (MPKB-BRI). By investigating management of human resources, the researcher will be able to know its effects on organizational commitment. This research focuses on five independent variables which were recruitment, selection, performance appraisal, training and development, and compensation while dependent variable was organizational commitment. This study was conducted using primary data as sources. The respondents were employees in MPKB-BRI with the total of 169 respondents. The technique used was convenience sampling. In other to gather the necessary data, the researcher used questionnaires that have been distributed to the respondents. The data will be analyzed using SPSS Statistics Data Editor and this study focused on frequency analysis, descriptive analysis, reliability analysis, Pearson correlation analysis, multiple regression analysis of data and hypotheses testing. The result shows recruitment and performance appraisal have positive relationship with organizational commitment. Furthermore, selection, training and development, and compensation have negative relationship with organizational commitment. In conclusion, recruitment and performance appraisal were supported by employees in MPKB-BRI.